Nationwide in-hospital mortality and morbidity analysis of COVID-19 in advanced chronic kidney disease, dialysis and kidney transplant recipients - He, Mingyue; Wang, Yichen; Li, Si; Gillespie, Avrum (Frontiers in Medicine, 2023)
Background Patients with advanced chronic kidney disease (CKD), end-stage kidney disease (ESKD), and kidney transplants (KT) are at an elevated risk for COVID-19 infection, hospitalization, and mortality. A comprehensive comparison of morbidity and mortality between these populations with kidney disease and individuals without any kidney disease is lacking. Methods We analysed the 2020 Nationwide Inpatient Sample (NIS) database for non-elective adult COVID-19 hospitalizations, categorizing patients into advanced CKD, ESKD, KT, and kidney disease-free cohorts. Our analysis included a description of the distribution of comorbidities across the entire spectrum of CKD, ESKD, and KT. Additionally, we investigated in-hospital mortality, morbidity, and resource utilization, adjusting for potential confounders through multivariable regression models. Results The study included 1,018,915 adults hospitalized for COVID-19 in 2020. The incidence of advanced CKD, ESKD, and KT in this cohort was 5.8%, 3.8%, and 0.4%, respectively. Patients with advanced CKD, ESKD, and KT exhibited higher multimorbidity burdens, with 90.3%, 91.0%, and 75.2% of patients in each group having a Charlson comorbidity index (CCI) equal to or greater than 3. The all-cause in-hospital mortality ranged from 9.3% in kidney disease-free patients to 20.6% in advanced CKD, 19.4% in ESKD, and 12.4% in KT patients. After adjusting for potential confounders at both the patient and hospital levels, CKD stages 3–5; ESKD; and KT were found to be associated with increased odds of mortality, with adjusted odds ratios (aOR) of 1.34, 1.80, 2.66, 1.97, and 1.69, respectively. Conclusion Patients hospitalized for COVID-19 with advanced CKD, ESKD, or KT demonstrated a higher burden of comorbidities and increased mortality rates compared to those without kidney disease. After adjusting for confounders, CKD stages 3–5; ESKD; and KT were identified as independent risk factors for in-hospital mortality, illustrating a dose-response relationship between the odds of mortality and adverse outcomes as CKD progressed from stages 3 to 5. Our study highlights the necessity for enhanced management of comorbidities, targeted interventions, and vigorous vaccination efforts to mitigate the risk of adverse outcomes in the vulnerable populations of patients with CKD, ESKD, and KT.